2018
DOI: 10.1021/acs.jpcb.8b00649
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Long-Distance Hydrogen-Bond Networks in Photosystem II

Abstract: Photosystem II uses the energy of absorbed light to split water molecules, generating molecular oxygen, electrons, and protons. The four protons generated during each reaction cycle are released to the lumen via mechanisms that are poorly understood. Given the complexity of photosystem II, which consists of multiple protein subunits and cofactor molecules and hosts numerous waters, a fundamental issue is finding transient networks of hydrogen bonds that bridge potential proton donor and acceptor groups. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 69 publications
2
64
0
Order By: Relevance
“…Functionally, PsbO stabilizes the Mn 4 CaO 5 cluster under suboptimal chloride concentrations and may also assist in maintaining the association of Ca 2+ with the WOC . It has also been suggested to play a role in proton transfer away from the WOC . Since high proton concentrations in the vicinity of the WOC are counterproductive in the water splitting process, a continuous removal of protons is required.…”
Section: Subunits Of the Core Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…Functionally, PsbO stabilizes the Mn 4 CaO 5 cluster under suboptimal chloride concentrations and may also assist in maintaining the association of Ca 2+ with the WOC . It has also been suggested to play a role in proton transfer away from the WOC . Since high proton concentrations in the vicinity of the WOC are counterproductive in the water splitting process, a continuous removal of protons is required.…”
Section: Subunits Of the Core Complexmentioning
confidence: 99%
“…The latter are local and probably do not affect the overall PSIIcc structure. The high conservation of accessible, negatively charged surface residues in PsbO suggests an additional function as local pH buffer or proton antenna . In a proton antenna, the surface carboxylate groups that are located close to each other might retain a proton for longer times than a single group.…”
Section: Subunits Of the Core Complexmentioning
confidence: 99%
“…In this work, it was found that all the water channels inside PSII have an activation energy for water permeation higher than the one in lipid membranes (Hub and De Groot 2008), thus suggesting that in PSII internal water diffusion is regulated, which is beneficial to stabilize the oxygen-evolving cluster during turnover. Atomistic MD simulations combined with in silico mutational analysis were used to characterize the role of specific residues and protonation states in controlling the long-distance hydrogenbond networks that connect the manganese cluster region to the lumen of the thylakoid (Guerra et al 2018).…”
Section: Beyond the μS Timescale: Interplay Between Pigment-protein Cmentioning
confidence: 99%
“…It has been suggested that the evolutionarily conserved extrinsic PSII subunit PsbO, which is located at the luminal side of PSII (Figure A), might provide a small buffering capacity or pathways for proton removal, or might act as a proton antenna, in addition to its established function in controlling the chloride and calcium concentrations at the OEC, thereby (and possibly also by other means) stabilizing the manganese complex . A pH buffer functionality of the PsbO carboxylate groups could transiently avoid acidification of the thylakoid lumen, for conditions of fluctuating light intensities (but not under continuous illumination), that easily and often occur in a natural habitat.…”
Section: Introductionmentioning
confidence: 99%
“…X‐ray crystallography and computation suggested an extended proton network around the OEC, serving as starting point for proton transport pathways towards the thylakoid lumen. PsbO interacts with subunits D1 and D2 of PSII through the loops Asp158–Lys188 and Asp222–Ala228, and their residues Asp158, Asp222–Asp224, His228, and Glu229 are part of a putative proton exit pathway . The smallest distance between PsbO and the OEC is 17 Å, as measured in a PSII crystal structure (PDB ID: 3WU2).…”
Section: Introductionmentioning
confidence: 99%